158k views
2 votes
Solve 6(z-1) + 14 = -40

User Smossen
by
4.7k points

2 Answers

6 votes
First lets start with subtracting 14 and getting it to the other side so -40 minus 14 would be -54 then we have 6(z-1)=-54 so we now gotta distribute 6 to z and 1 so we would have 6z-6=-54 next we would add the 6 to the other side which would make -48 so now for the final step we can divide the 6z by 6 and also divide -48 by 6 since you need to do it to both sides which would give us z=-8
User Surveon
by
5.1k points
5 votes

Answer:

z = -8

Explanation:

6(z-1) + 14 = -40

6z - 6 + 14 = -40 Distribute the 6

6z + 8 = -40 Combine Like Terms

6z = -48 Subtract 8 on Both Sides

z = -8 Divide by 6 on Both Sides

User Ahmed Soliman
by
5.1k points